Etiological profile and correlation of radiological and endoscopic modalities for evaluation of nasal obstruction: a hospital-based study - Sachdeva, Kavita; Varshney, Ruchir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Nasal obstruction causes considerable disease burden on our society and is frequently under-treated and under-evaluated. Aim of the study was to establish etiological profile and evaluate correlation of radiological and endoscopic modalities for evaluation of nasal obstruction. Methods: Ninety patients with nasal obstruction presenting to OPD of a tertiary hospital were evaluated with history/physical examination, rhinoscopy and radiological assessment by X-ray of para nasal sinuses (PNS), Computerized tomography of PNS (CT-PNS) and nasal endoscopy. Results: Inflammatory polyps were most common cause (33%) of nasal obstruction in our population which was young in age (20-40 years), the obstruction being predominantly of short duration (<10 months). CT-PNS had significantly better performance than X-ray PNS in detection of nasal polyp and cyst. There was good agreement between CT-PNS and nasal endoscopy for most of the cases. Polyps and mucosal oedema had significantly higher detection rates by endoscopy while CT-PNS was better in assessment of DNS. Conclusion: CT-PNS and Nasal endoscopy are superior for assessment of nasal obstruction and complement each other.